Association between socioeconomic factors and urinary sodium-to-potassium ratio: the Nagahama Study. Issue 11 (November 2018) - Yamashita, Makoto; Tabara, Yasuharu; Higo, Yukiko; Setoh, Kazuya; Kawaguchi, Takahisa; Takahashi, Yoshimitsu; Kosugi, Shinji; Nakayama, Takeo; Matsuda, Fumihiko; Wakamura, Tomoko
Abstract High sodium intake is a simple modifiable risk factor for hypertension. Although not confirmed, lower socioeconomic status may be a factor that increases sodium intake. We aimed to clarify the association between socioeconomic status and urinary sodium-to-potassium ratio by cross-sectional and longitudinal analyses. The study included 9410 community residents. Spot urine sodium-to-potassium ratios were measured twice with a 5-year interval. Socioeconomic status was investigated using a self-administered questionnaire. Cross-sectional analysis revealed that educational attainment was inversely associated with urinary sodium-to-potassium ratio (years of education ≤ 9: 3.0 ± 1.8,  ≤ 12: 2.9 ± 1.6,  ≥ 13: 2.8 ± 1.6;P  < 0.001), whereas no significant association was observed with household income. Men, particularly individuals living alone, exhibited markedly high sodium-to-potassium ratios (3.6 ± 2.3). Although frequent intake of vegetables, fruits, and dairy products was also inversely associated with the ratio, the associations with educational attainment ( ≤ 9: reference,  ≤ 12:β  = −0.032, P  = 0.026,  ≥ 13:β  =  −0.059, P  < 0.001), marital status (β  = −0.040, P  < 0.001), and sex*marital status interaction (β  = 0.054, P  = 0.001) were independent of these covariates. Educational attainment was also inversely associated with differences in the urinary sodium-to-potassium ratio during the follow-up period (odds ratio, 0.70;P  < 0.001). Lower educational attainment was an independent determinant for urinary sodium-to-potassium ratio. Health literacy education, particularly in men living alone, may be a factor for reducing salt intake even in high-income countries where equal educational opportunity is assured.